Anti‐leukaemic activity of the TYK2 selective inhibitor NDI‐031301 in T‐cell acute lymphoblastic leukaemia. (14th March 2017) - Akahane, Koshi; Li, Zhaodong; Etchin, Julia; Berezovskaya, Alla; Gjini, Evisa; Masse, Craig E.; Miao, Wenyan; Rocnik, Jennifer; Kapeller, Rosana; Greenwood, Jeremy R.; Tiv, Hong; Sanda, Takaomi; et al.
Summary: Activation of tyrosine kinase 2 (TYK2) contributes to the aberrant survival of T‐cell acute lymphoblastic leukaemia (T‐ALL) cells. Here we demonstrate the anti‐leukaemic activity of a novel TYK2 inhibitor, NDI‐031301. NDI‐031301 is a potent and selective inhibitor of TYK2 that induced robust growth inhibition of human T‐ALL cell lines. NDI‐031301 treatment of human T‐ALL cell lines resulted in induction of apoptosis that was not observed with the JAK inhibitors tofacitinib and baricitinib. Further investigation revealed that NDI‐031301 treatment uniquely leads to activation of three mitogen‐activated protein kinases (MAPKs), resulting in phosphorylation of ERK, SAPK/JNK and p38 MAPK coincident with PARP cleavage. Activation of p38 MAPK occurred within 1 h of NDI‐031301 treatment and was responsible for NDI‐031301‐induced T‐ALL cell death, as pharmacological inhibition of p38 MAPK partially rescued apoptosis induced by TYK2 inhibitor. Finally, daily oral administration of NDI‐031301 at 100 mg/kg bid to immunodeficient mice engrafted with KOPT‐K1 T‐ALL cells was well tolerated, and led to decreased tumour burden and a significant survival benefit. These results support selective inhibition of TYK2 as a promising potential therapeutic strategy for T‐ALL.